Resource-Aware Network Slicing for QoS-Driven Service Orchestration in Integrated Satellite–5G Systems - Q. Hugh; Freddy Soria (Electronics, Communications, and Computing Summit, 2025)
An overlap of satellite and terrestrial 5G infrastructure appears to be the solution to getting the needed nationwide and international coverage in wireless network communications of the next generation. Nonetheless, the non-homogeneity of resource availability, latency peculiarities, and link robustness of these domains is one of the key issues regarding providing consistent Quality of Service (QoS). This essay suggests a resource-aware network slicing architecture of QoS-based service/orchestration within integrated satellite-5G networks and, in particular, on the U.S.-based deployment scenarios of using satellite communications on rural broadband, public safety, and emergency connection. This architecture will use hierarchical orchestration, link-aware resource profiling, to dynamically assign resources within slices, to achieve end-to-end SLA compliance. By classifying services as latency, bandwidth and reliability calls, a QoS classifier can map services to the best slices and provide the best partitioning of resources. Slice isolation and adaptive routing are also integrated into the system to guard against failure of critical services under a varying link condition. The simulation outcomes on realistic mobility and load profiles based on FCC broadband access data and 3GPP satellite models allow showing that framework deploys a 35 percent increase of resource usage efficiency and 96 percent SLA-fulness of URLLC services over variable connectivity in terms of satellite connectivity. The proposed model incurs greater throughput and less variance of delay compared to static slicing. These results validate that dynamic, QoS-aware network slicing of U.S. integrated satellite and 5G networks can be achieved and form the basis to future extensions on AI-orchestration as well as multi-orbit satellite integration.